Property and “Nuda Potestas” as Constitutions of Reinach’s Philosophy of Law - Massa, Manuela (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
This contribution centers on the notions of property and nuda potestas in Reinach’s philosophy of law. I aim to demonstrate how both terms ground an important part of Reinach’s understanding of a priori condition for civil rights. Consequently, I assess the principle of property with a comparison to Luis de Molina, since he shows in his De Iustitia et Iure how dominium and rights justify some forms of property (lay and ecclesiastical) and political power (Molina 1659, disp2 n1; Kaufmann 2014, 129). Hence, the right of the person is discussed by following the potestas. In Die apriorischen Grundlagen des bürgerlichen Rechtes, Reinach implicitly refers to the nuda potestas, which is a kind of power that can be applied only formally and not in fact to something else and for that reason, it can only be caught a priori, since acts are performed by another person within it. This is the reason why the rights of a person can be divided between more people, and it is at first just a kind of property, which can be exercised upon the individual. Consequently, I divide my contribution as follows. First, in considering the social act, I show how its characteristics of Anspruch and Verbindlichkeit result from the commitment that human beings make to one another. In doing this, I discuss the particular condition of slavery through which it is possible to find the property and the nuda potestas since there is no enjoyment of the good to which it refers. Second, I apply both concepts by showing a parallel with Luis de Molina. This comes about in consideration of the case of dominium, in which absolute rights can be ascribed to their relative claim. Third and finally, I offer a critique of Reinach, in which I show how absolute rights and relative claims cannot be assimilated.